CN113683439B - Shell, preparation method thereof and electronic equipment - Google Patents

Shell, preparation method thereof and electronic equipment Download PDF

Info

Publication number
CN113683439B
CN113683439B CN202110917644.7A CN202110917644A CN113683439B CN 113683439 B CN113683439 B CN 113683439B CN 202110917644 A CN202110917644 A CN 202110917644A CN 113683439 B CN113683439 B CN 113683439B
Authority
CN
China
Prior art keywords
polymer
layer
ceramic
preparation
accelerator
Prior art date
Legal status (The legal status is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the status listed.)
Active
Application number
CN202110917644.7A
Other languages
Chinese (zh)
Other versions
CN113683439A (en
Inventor
滕双双
Current Assignee (The listed assignees may be inaccurate. Google has not performed a legal analysis and makes no representation or warranty as to the accuracy of the list.)
Guangdong Oppo Mobile Telecommunications Corp Ltd
Original Assignee
Guangdong Oppo Mobile Telecommunications Corp Ltd
Priority date (The priority date is an assumption and is not a legal conclusion. Google has not performed a legal analysis and makes no representation as to the accuracy of the date listed.)
Filing date
Publication date
Application filed by Guangdong Oppo Mobile Telecommunications Corp Ltd filed Critical Guangdong Oppo Mobile Telecommunications Corp Ltd
Priority to CN202110917644.7A priority Critical patent/CN113683439B/en
Publication of CN113683439A publication Critical patent/CN113683439A/en
Application granted granted Critical
Publication of CN113683439B publication Critical patent/CN113683439B/en
Active legal-status Critical Current
Anticipated expiration legal-status Critical

Links

Images

Classifications

    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B41/00—After-treatment of mortars, concrete, artificial stone or ceramics; Treatment of natural stone
    • C04B41/60—After-treatment of mortars, concrete, artificial stone or ceramics; Treatment of natural stone of only artificial stone
    • C04B41/61—Coating or impregnation
    • C04B41/65—Coating or impregnation with inorganic materials
    • C04B41/69—Metals
    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B26/00—Compositions of mortars, concrete or artificial stone, containing only organic binders, e.g. polymer or resin concrete
    • C04B26/02—Macromolecular compounds
    • C04B26/10—Macromolecular compounds obtained otherwise than by reactions only involving carbon-to-carbon unsaturated bonds
    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B35/00—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products
    • C04B35/01—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products based on oxide ceramics
    • C04B35/453—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products based on oxide ceramics based on zinc, tin, or bismuth oxides or solid solutions thereof with other oxides, e.g. zincates, stannates or bismuthates
    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B35/00—Shaped ceramic products characterised by their composition; Ceramics compositions; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products
    • C04B35/622—Forming processes; Processing powders of inorganic compounds preparatory to the manufacturing of ceramic products
    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B41/00—After-treatment of mortars, concrete, artificial stone or ceramics; Treatment of natural stone
    • C04B41/45—Coating or impregnating, e.g. injection in masonry, partial coating of green or fired ceramics, organic coating compositions for adhering together two concrete elements
    • C04B41/459—Temporary coatings or impregnations
    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B41/00—After-treatment of mortars, concrete, artificial stone or ceramics; Treatment of natural stone
    • C04B41/45—Coating or impregnating, e.g. injection in masonry, partial coating of green or fired ceramics, organic coating compositions for adhering together two concrete elements
    • C04B41/50—Coating or impregnating, e.g. injection in masonry, partial coating of green or fired ceramics, organic coating compositions for adhering together two concrete elements with inorganic materials
    • C04B41/51—Metallising, e.g. infiltration of sintered ceramic preforms with molten metal
    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B41/00—After-treatment of mortars, concrete, artificial stone or ceramics; Treatment of natural stone
    • C04B41/45—Coating or impregnating, e.g. injection in masonry, partial coating of green or fired ceramics, organic coating compositions for adhering together two concrete elements
    • C04B41/52—Multiple coating or impregnating multiple coating or impregnating with the same composition or with compositions only differing in the concentration of the constituents, is classified as single coating or impregnation
    • C—CHEMISTRY; METALLURGY
    • C04—CEMENTS; CONCRETE; ARTIFICIAL STONE; CERAMICS; REFRACTORIES
    • C04B—LIME, MAGNESIA; SLAG; CEMENTS; COMPOSITIONS THEREOF, e.g. MORTARS, CONCRETE OR LIKE BUILDING MATERIALS; ARTIFICIAL STONE; CERAMICS; REFRACTORIES; TREATMENT OF NATURAL STONE
    • C04B41/00—After-treatment of mortars, concrete, artificial stone or ceramics; Treatment of natural stone
    • C04B41/60—After-treatment of mortars, concrete, artificial stone or ceramics; Treatment of natural stone of only artificial stone
    • C04B41/61—Coating or impregnation
    • C04B41/70—Coating or impregnation for obtaining at least two superposed coatings having different compositions
    • H—ELECTRICITY
    • H05—ELECTRIC TECHNIQUES NOT OTHERWISE PROVIDED FOR
    • H05K—PRINTED CIRCUITS; CASINGS OR CONSTRUCTIONAL DETAILS OF ELECTRIC APPARATUS; MANUFACTURE OF ASSEMBLAGES OF ELECTRICAL COMPONENTS
    • H05K5/00—Casings, cabinets or drawers for electric apparatus

Landscapes

  • Chemical & Material Sciences (AREA)
  • Engineering & Computer Science (AREA)
  • Ceramic Engineering (AREA)
  • Materials Engineering (AREA)
  • Structural Engineering (AREA)
  • Organic Chemistry (AREA)
  • Inorganic Chemistry (AREA)
  • Manufacturing & Machinery (AREA)
  • Microelectronics & Electronic Packaging (AREA)
  • Chemical Kinetics & Catalysis (AREA)
  • Compositions Of Macromolecular Compounds (AREA)

Abstract

本申请提供了一种壳体的制备方法,包括:将聚合物陶瓷坯体涂覆和/或浸泡前处理液,经干燥后在所述聚合物陶瓷坯体表面形成前处理层,得到复合坯体,其中,所述聚合物陶瓷坯体包括聚合物,所述前处理液包括能够促进所述聚合物交联的促进剂;所述复合坯体经过热处理和热压后,再去除所述前处理层,得到聚合物陶瓷层,制得壳体。通过前处理液处理聚合物陶瓷坯体后,在其表面形成了前处理层,从而可以在后续热处理过程中,提高聚合物陶瓷坯体中聚合物的交联程度,同时大幅度降低热处理的时间,进而在提升壳体机械性能的同时又降低了壳体的制备时长。本申请还提供了一种壳体和电子设备。

Figure 202110917644

The present application provides a method for preparing a shell, comprising: coating and/or soaking a polymer ceramic body in a pretreatment liquid, and after drying, a pretreatment layer is formed on the surface of the polymer ceramic body to obtain a composite body body, wherein the polymer ceramic body includes a polymer, and the pretreatment liquid includes an accelerator capable of promoting the cross-linking of the polymer; after the composite body is heat-treated and hot-pressed, the pretreatment The layer is treated to obtain a polymer ceramic layer, and a shell is produced. After the polymer ceramic body is treated with the pretreatment liquid, a pretreatment layer is formed on its surface, so that in the subsequent heat treatment process, the degree of crosslinking of the polymer in the polymer ceramic body can be improved, and the heat treatment time can be greatly reduced. , thereby improving the mechanical properties of the casing and reducing the preparation time of the casing. The present application also provides a housing and an electronic device.

Figure 202110917644

Description

Shell, preparation method thereof and electronic equipment
Technical Field
The application belongs to the technical field of electronic products, and particularly relates to a shell, a preparation method of the shell and electronic equipment.
Background
With the increase of the consumer level, consumers have demanded more and more electronic products with diversified functions, appearance, texture, and the like. In recent years, ceramic materials have been the focus of research on electronic device housings due to their warm and moist texture. In the related art, the product is prepared by the composite material formed by the resin and the ceramic material, but the preparation period of the product is long at present, and the strength of the product is different from that of a real ceramic product. Therefore, the ceramic shell and the preparation method thereof still need to be improved.
Disclosure of Invention
In view of this, the present application provides a housing, a method for manufacturing the same, and an electronic device.
In a first aspect, the present application provides a method for preparing a housing, comprising: coating and/or soaking a pretreatment liquid on a polymer ceramic blank, and drying to form a pretreatment layer on the surface of the polymer ceramic blank to obtain a composite blank, wherein the polymer ceramic blank comprises a polymer, and the pretreatment liquid comprises an accelerator capable of accelerating the crosslinking of the polymer; and after the composite blank is subjected to heat treatment and hot pressing, removing the pretreatment layer to obtain a polymer ceramic layer, and preparing the shell.
In a second aspect, the present application provides a housing made by the method of the first aspect, the housing comprising a polymeric ceramic layer.
In a third aspect, the present application provides an electronic device comprising the housing of the second aspect.
After a polymer ceramic blank is treated by a pretreatment liquid, a pretreatment layer is formed on the surface of the polymer ceramic blank, so that the degree of crosslinking of a polymer in the polymer ceramic blank can be improved in the subsequent heat treatment process, the heat treatment time is greatly reduced, the mechanical property of the shell is improved, and the preparation time of the shell is reduced; the electronic equipment with the shell has excellent mechanical performance and can better meet the requirements of users.
Drawings
In order to more clearly explain the technical solution in the embodiments of the present application, the drawings that are required to be used in the embodiments of the present application will be described below.
Fig. 1 is a flowchart of a method for manufacturing a housing according to an embodiment of the present disclosure.
Fig. 2 is a flowchart of a method for manufacturing a polymer ceramic green body according to an embodiment of the present disclosure.
Fig. 3 is a flow chart of a method for preparing a polymer ceramic green body according to another embodiment of the present disclosure.
Fig. 4 is a schematic structural diagram of a housing according to an embodiment of the present application.
Fig. 5 is a schematic structural diagram of a housing according to another embodiment of the present application.
Fig. 6 is a schematic structural diagram of an electronic device according to an embodiment of the present application.
Fig. 7 is a schematic structural diagram of an electronic device according to an embodiment of the present application.
Detailed Description
The following is a preferred embodiment of the present application, and it should be noted that, for those skilled in the art, various modifications and embellishments can be made without departing from the principle of the present application, and these modifications and embellishments are also regarded as the scope of the present application.
The following disclosure provides many different embodiments or examples for implementing different features of the application. In order to simplify the disclosure of the present application, specific example components and arrangements are described below. Of course, they are merely examples and are not intended to limit the present application. Moreover, the present application may repeat reference numerals and/or letters in the various examples, such repetition is for the purpose of simplicity and clarity and does not in itself dictate a relationship between the various embodiments and/or configurations discussed. In addition, the present application provides examples of various specific processes and materials, but one of ordinary skill in the art may recognize applications of other processes and/or use of other materials.
Referring to fig. 1, a flow chart of a method for manufacturing a housing according to an embodiment of the present disclosure includes:
s101: coating and/or soaking a polymer ceramic blank with pretreatment liquid, and drying to form a pretreatment layer on the surface of the polymer ceramic blank to obtain a composite blank, wherein the polymer ceramic blank comprises a polymer, and the pretreatment liquid comprises an accelerator capable of accelerating polymer crosslinking.
S102: and after the composite blank is subjected to heat treatment and hot pressing, removing the pretreatment layer to obtain a polymer ceramic layer, and thus obtaining the shell.
In the application, after the polymer ceramic body is treated by the pretreatment liquid, the accelerator in the pretreatment liquid can promote the crosslinking of the polymer in the polymer ceramic body in the heat treatment process, and meanwhile, the heat treatment time is greatly reduced, so that the mechanical property of the prepared shell 100 can be improved, the preparation time is greatly shortened, and the preparation efficiency is improved. In the related art, various materials such as glass, metal, plastic, and ceramic can be used in the electronic device 200, but the glass has high dielectric loss, has a certain limitation in millimeter wave use, and the anti-drop performance of the glass needs to be improved; the metal can shield the product signal due to the conduction; the texture of the plastic needs to be improved; the high dielectric constant of the ceramic can cause signal damage to a great extent. In the present application, by providing the polymer ceramic layer 10, the high-grade texture of the ceramic is maintained, and the dielectric properties meet the requirements of millimeter waves so as to meet the requirements of 5G communication technology. Meanwhile, the inventor of the present application finds that the polymer ceramic layer 10 has low surface hardness, poor scratch resistance, insufficient product strength, incapability of realizing thin thickness, long overall processing time and low production efficiency; therefore, the inventor of the present application coats and/or soaks the polymer ceramic body with the pretreatment liquid, so that in the heat treatment process, the accelerator in the pretreatment liquid can promote the crosslinking of the polymer in the polymer ceramic body, and improve the crosslinking degree of the polymer, so that the heat treatment duration can be greatly reduced, the production efficiency can be improved, the hardness of the shell 100 can be improved, the scratch resistance can be improved, and the application of the shell can be facilitated.
In S101, a composite body is obtained by coating and/or soaking the polymer ceramic body with a pretreatment liquid, drying and then forming a pretreatment layer on the surface of the polymer ceramic body. Through pretreatment, a pretreatment layer is formed on the surface of the polymer ceramic body, the polymer ceramic body comprises a polymer, and the pretreatment layer is provided with an accelerant capable of promoting the crosslinking of the polymer, so that the crosslinking of the polymer can be promoted in the subsequent heat treatment process, and the crosslinking degree is improved.
Referring to fig. 2, a flow chart of a method for preparing a polymer ceramic body according to an embodiment of the present application is provided, which includes:
s1011: and mixing the ceramic particles and the polymer, and granulating to obtain the injection molding feed.
S1012: and injection molding the feed to obtain a polymer ceramic blank.
In S1011, the injection molding feed is formed by mixing and granulating the ceramic particles and the polymer, which is beneficial to the subsequent injection molding.
In an embodiment of the present application, the ceramic particles include at least one of zinc oxide, zirconium oxide, aluminum oxide, silicon dioxide, titanium oxide, and silicon carbide. The ceramic particles are high temperature resistant, corrosion resistant, high in hardness and good in strength, and are beneficial to improving the performance of the shell 100. In an embodiment, the refractive index of the ceramic particles is greater than 2, which is favorable for further improving the ceramic texture of the casing 100. In the present embodiment, the ceramic particles have a diameter of 20nm to 1 μm. The selection of the above-mentioned size of the ceramic particles facilitates mixing with the polymer and also facilitates increasing the ceramic phase content of the shell 100. Further, the diameter of the ceramic particles is 100nm to 800nm. Further, the ceramic particles have a diameter of 300nm to 600nm. Specifically, the diameter of the ceramic particles may be, but not limited to, 50nm, 100nm, 250nm, 400nm, 500nm, 650nm, 700nm, 800nm, 900nm, 1 μm, or the like. It is understood that the morphology of the ceramic particles may be, but is not limited to, spherical, spheroidal, etc.
In the present application, by mixing the ceramic particles with the polymer, it is advantageous to reduce the quality of the case 100 while improving the toughness of the case 100. In an embodiment of the present application, the polymer comprises a thermoplastic resin comprising at least one of polyphenylene sulfide, polyphenylene sulfone, polyamide, and ethylene vinyl acetate. The physical and chemical properties of the thermopolymer can be matched with the preparation process of the shell 100, decomposition cannot occur in the preparation process, the difficulty of the preparation process cannot be increased, and the production cost can be reduced.
It is understood that, when the ceramic particles and the polymer are mixed, the mixing ratio of the ceramic particles and the polymer may be selected according to the content of each substance in the polymer ceramic layer 10, and is not limited thereto. In one embodiment, the mass ratio of ceramic particles to polymer is (0.5-0.8): (0.2-0.5) is favorable for preparing the polymer ceramic layer 10 with high hardness, good strength and strong ceramic texture. In one embodiment, 50% -80% by mass of the ceramic particles are mixed with 20% -50% of the polymer to form a mixture.
In embodiments herein, mixing comprises at least one of blending and banburying. Specifically, mixing may be performed in at least one of a blending extruder and an internal mixer to uniformly disperse the respective substances in the mixture. In one embodiment, the mixture is blended and/or banned 2-5 times, with the duration of one blend or banburying being 1h-2h. Specifically, the temperature for blending or banburying is 300-350 ℃. In the application, the injection molding feed can be obtained by granulating the mixed material. In one embodiment, the ceramic particles and the polymer may be mixed and then placed in an internal mixing and granulating machine, and the injection molding feed is obtained after internal mixing and granulating. Specifically, the temperature of banburying granulation can be but is not limited to 200 ℃ to 350 ℃, and the time of banburying granulation can be but is not limited to 1h to 12h. Furthermore, the banburying process is in a negative pressure state, and the absolute value of the pressure is less than 0.01MPa, so that the polymer is effectively prevented from being oxidized, and the elimination of gas generated by side reaction can be effectively promoted.
In S1012, the injection molding process parameters may be selected according to the properties of the selected polymer. In an embodiment of the application, the method further comprises drying the injection molding feed before injection molding. In one embodiment, the drying treatment comprises drying at 90-150 ℃ for 8-12 h. The water in the injection molding feed is removed through a drying process. In one embodiment of the present application, when the polymer comprises at least one of polyphenylene sulfide, polyphenylene sulfone, polyamide and ethylene-vinyl acetate copolymer, the injection molding temperature is 320 ℃ to 360 ℃, the injection speed is 70% to 100%, and the injection pressure is 120MPa to 250MPa; the temperature of the die is 130-180 ℃, and the pressure maintaining time is 2-60 s, so as to obtain the polymer ceramic blank. Further, the molding temperature of the injection molding is 320-340 ℃, the injection speed is 70-90%, and the injection pressure is 150-200 MPa; the temperature of the die is 140-170 ℃, and the pressure maintaining time is 5-50 s, so as to obtain the polymer ceramic blank. The polymer ceramic blank with good molding effect and high molding yield can be obtained by adopting the conditions for injection molding. The shape of the polymer ceramic body obtained by injection molding can be selected according to the requirement, and the thickness of the polymer ceramic body can also be selected according to the requirement. It is understood that other forming methods such as tape casting and the like can be adopted to prepare the polymer ceramic body. In the application, the injection molding method is simpler to operate, the compatibility problem between a solvent and a polymer phase does not need to be considered in comparison with tape casting, and the preparation cost is low.
Referring to fig. 3, a flow chart of a method for manufacturing a polymer ceramic green body according to another embodiment of the present application is provided, which includes:
s2010: and (4) pretreating the ceramic particles to obtain the treated ceramic particles.
S2011: and mixing the treated ceramic particles with a polymer, and granulating to obtain the injection molding feed.
S2012: and injection molding the feed to obtain a polymer ceramic blank.
In S1011, the injection molding feed is formed by mixing and granulating the ceramic particles and the polymer, which is beneficial to the subsequent injection molding.
It is to be understood that the detailed descriptions of S2011 and S2012 refer to the descriptions of the corresponding parts of S1011 and S1012 in the above embodiments, and are not repeated herein.
In one embodiment of the present application, the pre-treating the ceramic particles to obtain treated ceramic particles comprises: and carrying out modification treatment on the ceramic particles, and carrying out spray granulation to obtain the treated ceramic particles. By modifying the ceramic particles, the compatibility of the ceramic particles with the polymer is improved, thereby improving the performance of the housing 100.
In one embodiment of the present application, the ceramic particles are modified by mixing the ceramic particles with a modifying agent. Optionally, the modifier comprises at least one of a silane coupling agent, ammonium citrate, polyacrylic acid, ammonium polymethacrylate, and triethanolammonium. In the present application, the modifier may be selected according to the properties of the polymer. In another embodiment of the present application, when the ceramic particles are mixed with the modifier, the ceramic particles are 60 to 98 parts by weight and the modifier is 0.1 to 3 parts by weight. The mixing ratio can be such that the ceramic particles are completely modified and the modifier is not agglomerated. Furthermore, when the ceramic particles and the modifier are mixed, the weight portions of the ceramic particles are 60 to 80 portions, and the weight portions of the modifier are 0.5 to 2 portions. In another embodiment of the present application, a dispersing aid is further added when the ceramic particles are mixed with the modifier, so that the ceramic particles are better uniformly dispersed. Specifically, the ceramic particles are 60 to 98 parts by weight, the modifier is 0.1 to 3 parts by weight, and the dispersing aid is 0.1 to 1 part by weight when the ceramic particles are mixed. In yet another embodiment of the present application, a colorant is added to the ceramic particles when they are mixed with the modifier, so that the apparent color of the polymer ceramic body can be improved. Specifically, the ceramic particles are 60 to 98 parts by weight, the modifier is 0.1 to 3 parts by weight, and the colorant is 1 to 20 parts by weight when the ceramic particles and the modifier are mixed. In the present application, the colorant includes at least one of an organic colorant and an inorganic colorant, and the colorant may be selected according to a desired color, for example, the colorant may be selected from cobalt oxide or carbon black, etc., to make the polymer ceramic body black, and the colorant may be, but not limited to, at least one selected from iron oxide, cerium oxide, nickel oxide, bismuth oxide, zinc oxide, manganese oxide, chromium oxide, copper oxide, vanadium oxide, and tin oxide, etc. In another embodiment of the present application, when the ceramic particles are mixed with the modifier, a dispersant and a colorant are further added, wherein the ceramic particles are 60 to 98 parts, the modifier is 0.1 to 3 parts, the dispersing aid is 0.1 to 1 part, and the colorant is 1 to 20 parts.
In another embodiment of the present application, the ceramic particles are mixed with the modifier to obtain a mixed material, and the mixed material is ball-milled to obtain a mixed slurry. It will be appreciated that when a dispersant and/or a colorant is added, a mixed material is obtained after all the substances are mixed, and the mixed material is then ball milled. Optionally, the ball milling comprises mixing the mixed material, water and ball milling beads, and ball milling for 12h-48h to completely modify the ceramic particles. In one embodiment, the mass ratio of the mixed material, water and ball milling beads is 1: (1-3): (0.5-1), which is beneficial to the full mixing of the mixed materials and the modification of the ceramic particles. Specifically, the mass ratio of the mixed material, water and ball milling beads can be, but is not limited to, 1. In the present application, the ball milling may be carried out at room temperature, e.g., 15 ℃ to 35 ℃, etc.
In yet another embodiment of the present application, the slurry is mixed to obtain treated ceramic particles after spray granulation. Specifically, the temperature of spray granulation may be selected according to the temperature of the solvent in the mixed slurry, and spray granulation may be performed in a spray granulator. In one embodiment, the feeding temperature is 70-80 ℃, the air inlet temperature is 130-160 ℃, the air outlet temperature is 70-85 ℃, the temperature in the tower is 70-90 ℃ and the negative pressure in the tower is 50-150 pa in the spray granulation process. Through the process, the treated ceramic particles with uniform sizes can be formed, and the mixing between the ceramic particles and the polymer is facilitated. Specifically, after spray granulation, the diameter of the treated ceramic particles is 100nm-1 μm.
In an embodiment of the present application, a polymer ceramic body includes a polymer and ceramic particles. Further, the ceramic particles are uniformly dispersed in the polymer ceramic body.
In S101, the pretreatment liquid includes an accelerator capable of accelerating crosslinking of the polymer. In embodiments herein, the accelerator comprises at least one of an organic accelerator and a metallic accelerator to promote crosslinking of the polymer. In one embodiment, the organic accelerator includes at least one of amines, phenols, benzenes, and ethers. Specifically, the organic accelerator includes at least one of melamine, hexamethoxymethyl melamine, trihydroxybenzene, pentaerythritol triallyl ether, phenol, and hindered phenols. In another embodiment, the metal promoter includes at least one of silver, copper, iron, lead, zinc, and magnesium. In the present application, the pretreatment liquid may contain only an organic accelerator, and may contain only a metal accelerator; it is also possible to include both organic and metallic promoters. The inventor of the application discovers that the crosslinking speed can be further increased by adding the organic promoter and the metal promoter at the same time, a higher crosslinking level can be achieved in the same time, the processing time is further reduced, and the preparation time is shortened. In one embodiment, the mass ratio of the organic promoter to the metal promoter in the accelerator is 1.2 to 4, thereby facilitating rapid increase in the degree of crosslinking of the polymer in subsequent heat treatment. Further, the mass ratio of the organic promoter to the metal promoter in the promoter is 1.5-3.5. Specifically, the mass ratio of the organic promoter to the metal promoter in the promoter may be, but is not limited to, 1.5, 2, 2.5, 2.8, 3, 3.4, 3.5, or the like. In a specific embodiment, melamine and zinc may be mixed in a mass ratio of 1.2 to 4 as an accelerator. In another embodiment of the present application, the accelerator is present in the pretreatment in an amount of 10 to 50% by mass. The accelerator with the content can effectively promote the crosslinking of the polymer in the subsequent treatment process, and can be well dispersed in the pretreatment liquid. Further, the mass content of the accelerator in the pretreatment is 15-45%. Furthermore, the mass content of the accelerator in the pretreatment is 20-40%. Specifically, the mass content of the accelerator in the pretreatment may be, but not limited to, 15%, 18%, 22%, 25%, 27%, 30%, 35%, 40%, 43%, or the like.
In one embodiment of the present application, the pretreatment liquid includes a solvent. In one embodiment, the mass content of the solvent in the pretreatment liquid is 50% to 80%. Further, the mass content of the solvent in the pretreatment liquid is 60-80%. Furthermore, the mass content of the solvent in the pretreatment liquid is 65-75%. Specifically, the mass content of the solvent in the pretreatment may be, but not limited to, 52%, 55%, 57%, 60%, 63%, 65%, 70%, 76%, 79%, or the like. In the present application, the solvent includes at least one of water, ethanol, and acetone. In another embodiment of the present application, the pretreatment liquid includes a dispersant. The uniform dispersion degree of the accelerator is improved by adding the dispersant. In one embodiment, the mass content of the dispersant in the pretreatment liquid is 0.5% to 5%. Further, the mass content of the dispersing agent in the pretreatment liquid is 1-3.5%. Specifically, the mass content of the dispersant in the pretreatment may be, but not limited to, 0.5%, 1%, 1.8%, 2%, 2.5%, 3%, 3.7%, 4%, 4.5%, or the like. In another embodiment, the dispersant includes at least one of a silane coupling agent, stearic acid, ammonium stearate, and polyethylene glycol. In another embodiment of the present application, the pretreatment liquid includes a binder. The accelerant is attached to the surface of the polymer ceramic body after spraying and soaking by adding the binder. In one embodiment, the mass content of the binder in the pretreatment liquid is 1% to 5%. Furthermore, the mass content of the binder in the pretreatment liquid is 1.5-4%. Furthermore, the mass content of the binder in the pretreatment liquid is 2-3.5%. Specifically, the mass content of the binder in the pretreatment may be, but not limited to, 1%, 1.8%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 4.7%, or the like. In another embodiment, the binder comprises at least one of polyvinyl alcohol, polyvinyl butyral, polyethylene glycol, and acrylic resin. In one embodiment, the pretreatment liquid includes an accelerator, a dispersant, a binder, and a solvent. Furthermore, the mass content of the accelerator in the pretreatment liquid is 10-50%, the mass content of the dispersant is 0.5-5%, the mass content of the binder is 1-5%, and the mass content of the solvent is 50-80%, so that the uniform dispersion of the accelerator can be ensured, and the accelerator can be attached to the surface of the polymer ceramic blank after the polymer ceramic blank is treated.
In the application, the pretreatment liquid may be coated on the surface of the polymer ceramic body by a coating method, or the polymer ceramic body may be immersed in the pretreatment liquid, so that a pretreatment layer may be formed on the surface of the polymer ceramic body after drying. In the embodiment of the application, the coating and/or soaking comprises treatment for 1-2 h at 15-40 ℃ so that the pretreatment liquid can be uniformly attached to the polymer ceramic blank. Further, the coating and/or soaking comprises treating at 20-35 ℃ for 1-2 h. In an embodiment of the application, the drying comprises a treatment at 80 ℃ to 100 ℃. Further, the drying includes treatment at 85 ℃ to 100 ℃. Specifically, the drying time can be selected according to the volatilization condition of the solvent.
In the embodiment of the present application, the thickness of the pretreatment layer is 10 μm to 100. Mu.m. Specifically, the thickness of the pretreatment layer may be, but not limited to, 10 μm, 20 μm, 40 μm, 50 μm, 70 μm, 85 μm, 100 μm, or the like. The pretreatment layer with the thickness can promote the crosslinking of the polymer in the subsequent heat treatment process, and meanwhile, the waste is avoided. The composite body is a polymer ceramic body and a pretreatment layer arranged on the surface of the polymer ceramic body. It is understood that the pretreatment layer can be disposed on one or more surfaces of the polymer ceramic body, or on all surfaces of the polymer ceramic body, and can be selected as desired.
In S102, crosslinking the polymer in the polymer ceramic blank through heat treatment, and accelerating the crosslinking degree of the polymer and reducing the heat treatment time under the action of an accelerator; and internal pores are eliminated after hot pressing, so that the density is improved; further, the pre-treatment layer is removed to obtain the polymer ceramic layer 10, and the housing 100 is manufactured.
In an embodiment of the present application, the time of the heat treatment is less than or equal to 12h. Further, the time of the heat treatment is less than or equal to 8 hours. Further, the time of the heat treatment is less than or equal to 5 hours. In the related technology, the crosslinking degree of the polymer is improved through heat treatment, the heat treatment time is 48-72 h, the preparation time is greatly prolonged, and the production efficiency is reduced. The inventor of the application discovers that the accelerator reacts with the polymer in the heat treatment process by arranging the pretreatment layer on the surface of the polymer ceramic blank, so that the crosslinking of the polymer is further promoted on the basis of the original crosslinking of the polymer, and the integral crosslinking degree is improved; compared with a polymer ceramic blank which is not treated by the pretreatment liquid, the polymer ceramic layer 10 prepared from the composite blank has the advantages of higher crosslinking degree of the polymer, high surface hardness, good scratch resistance effect and good overall strength, and meanwhile, the heat treatment time is greatly shortened and is less than or equal to 12 hours.
In one embodiment of the present application, the temperature of the heat treatment is greater than the melting temperature of the polymer and less than the decomposition temperature of the polymer. In another embodiment of the application, the heat treatment comprises raising the temperature from 15 ℃ to 40 ℃ to 220 ℃ to 280 ℃ within 0.5h to 1h, then preserving the heat for 0.5h to 2h, raising the temperature from 220 ℃ to 280 ℃ to 300 ℃ to 380 ℃ within 0.5h to 1h, and then preserving the heat for 0.5h to 4h. By adopting the segmented heat treatment process, the composite body can be heated uniformly, and the crosslinking degree of the polymer is uniform. In the first stage, the polymer in the polymer ceramic blank is pre-softened, and the accelerator in the pre-treatment layer can permeate into the polymer ceramic blank to react with the polymer; in the second stage, the temperature is increased and further cross-linking between the polymers occurs, thereby increasing the surface hardness and overall strength of the housing 100. In one embodiment, when the polymer ceramic bodies are subjected to heat treatment, the heat treatment comprises raising the temperature from 15 ℃ to 40 ℃ to 220 ℃ to 280 ℃ within 0.5h to 1h, then preserving the heat for 24h, raising the temperature from 220 ℃ to 280 ℃ to 300 ℃ to 380 ℃ within 0.5h to 1h, and then preserving the heat for 24h, wherein the heat treatment time is far longer than the heat treatment time. In one embodiment, when the polymer comprises at least one of polyphenylene sulfide, polyphenylene sulfone, polyamide and ethylene-vinyl acetate copolymer, the heat treatment process described above can be employed, greatly reducing the heat treatment duration and increasing the degree of crosslinking of the polymer.
In this application, through the inside compactness of hot pressing promotion, reduced inside micro defect, improved the intensity of casing 100. In embodiments of the present application, the temperature of the hot pressing is greater than the glass transition temperature of the polymer and less than the decomposition temperature of the polymer. Further, the hot pressing temperature is 20 ℃ to 60 ℃ higher than the glass transition temperature of the polymer. Within this range, the polymer is in a high elastic state, and the molecular chains can move to make the space between the polymer and the ceramic particles more compact under the action of pressure, thereby improving the performance of the shell 100. In one embodiment of the application, the hot pressing comprises treating at 300 ℃ -400 ℃ for 2h-12h at 20MPa-80 MPa. By adopting the hot pressing process, the compactness degree in the polymer ceramic layer 10 can be enhanced, and the strength of the shell 100 is further improved. Further, the hot pressing comprises the step of treating for 3 to 10 hours at the temperature of between 310 and 460 ℃ and under the pressure of between 30 and 70 MPa. Specifically, the pressure of hot pressing can be, but is not limited to, 28MPa, 35MPa, 40MPa, 45MPa, 50MPa, 60MPa, 75MPa, etc., the temperature of hot pressing can be, but is not limited to, 310 ℃, 320 ℃, 340 ℃, 350 ℃, 360 ℃ or 380 ℃, etc., and the time of hot pressing can be, but is not limited to, 2h, 4h, 5h, 7h, 10h, 11h, etc. In another embodiment of the present application, when the polymer includes at least one of polyphenylene sulfide, polyphenylene sulfone, polyamide, and ethylene-vinyl acetate copolymer, the hot pressing process described above may be employed. Specifically, the hot pressing may be performed in, but not limited to, a hot pressing sintering furnace, and the whole process is performed under an inert atmosphere, such as nitrogen or argon may be introduced. In the present application, after hot pressing, the polymer ceramic layer 10 can be removed after natural cooling.
In the present application, the polymer ceramic layer 10 having high surface hardness and high strength can be obtained by removing the pretreatment layer after hot pressing. In the embodiment of the present application, the pre-treatment layer is removed by at least one of computer numerically controlled precision machining (CNC machining) and lapping and polishing. The pre-treatment layer can be removed by CNC processing and the final desired assembled fit of the polymeric ceramic layer 10 is obtained; the polymeric ceramic layer 10 is made more flat, for example by CNC machining. The process conditions of the CNC machining can be selected as required. In a specific embodiment, the polymer ceramic body after hot pressing is subjected to CNC machining according to a required shape, wherein the CNC machining is performed by a polycrystalline diamond (PCD) milling cutter, the rotating speed of a main shaft is 10000-25000 rpm, and the single cutting amount is 10-500 mu m. By grinding and polishing, not only the pretreatment layer can be removed, but also the roughness of the surface of the polymer ceramic layer 10 can be reduced. In the application, a five-axis grinding and polishing machine, a 13.6B double-face grinding machine or a sweeping machine and the like can be selected for processing. In one embodiment, the lapping polishing includes rough polishing and fine polishing. Specifically, the rough polishing can be at least one of a sweeping machine, a double-sided grinder and a five-axis polisher, the polishing disc is selected from one or more of pig hair, a buffing disc, damping cloth, glue silk, copper wire, a carpet or a composite material of pig hair and buffing, the rough polishing liquid comprises at least one of water-system diamond polishing liquid and oil-system diamond polishing liquid, the granularity of diamond micro powder in the rough polishing liquid is 0.5-20 mu m, and the concentration of the rough polishing liquid is 1-30 wt%; the fine polishing can be at least one of a sweeping machine and a double-sided grinder, the fine polishing liquid comprises at least one of silicon oxide polishing liquid and cerium oxide polishing liquid, the particle size of particles in the fine polishing liquid is 50-500 nm, and the concentration of the fine polishing liquid is 5-45 wt%. In one embodiment, the CNC machining may be performed first, and then the grinding and polishing may be performed, so that the pre-treatment layer may be effectively removed, and the smooth surface of the polymer ceramic layer 10 may be obtained.
In the embodiment of the present application, the method for manufacturing the housing 100 further includes spraying or depositing a protective material on the surface of the polymer ceramic layer 10 to form the protective layer 20; specifically, the thickness of the protective layer 20 may be, but is not limited to, 0.5 μm to 3 μm, and the deposition may be, but is not limited to, evaporation coating, sputtering, vacuum plating, and the like. In one embodiment, the anti-fingerprint layer is formed by coating the anti-fingerprint agent on the surface of the polymer ceramic layer 10, so as to enhance the anti-fingerprint effect of the casing 100. In another embodiment, the hardened layer is formed by evaporating a hardening material on the surface of the polymer ceramic layer 10. Specifically, the hardened material may include, but is not limited to, at least one of graphite, alumina, zirconia, silica, chromium nitride, and titanium nitride.
The present application further provides a housing 100, which is manufactured by the manufacturing method according to any of the above embodiments, wherein the housing 100 includes the polymer ceramic layer 10. Referring to fig. 4, a schematic structural diagram of a housing 100 according to an embodiment of the present disclosure is shown, in which the housing 100 includes a polymer ceramic layer 10. The shell 100 provided by the application has the advantages of high surface hardness, good strength, good ceramic texture and wide application prospect.
In the present embodiment, the polymer ceramic layer 10 includes polymer and ceramic particles. In one embodiment, the polymer in the polymer ceramic layer 10 is crosslinked into a three-dimensional network structure, and the ceramic particles are dispersed in the three-dimensional network structure. In an embodiment of the present application, the polymer comprises a thermoplastic resin comprising at least one of polyphenylene sulfide, polyphenylene sulfone, polyamide, and ethylene vinyl acetate.
In the present embodiment, the mass content of the ceramic particles in the polymer ceramic layer 10 is 40% or more. The polymer ceramic layer 10 contains a large amount of ceramic particles, which can improve the surface hardness and the texture of the ceramic. Further, the mass content of the ceramic particles in the polymer ceramic layer 10 is 40% to 80%. Specifically, the mass content of the ceramic particles in the polymer ceramic layer 10 may be, but is not limited to, 40%, 45%, 50%, 58%, 60%, 65%, 72%, 75%, 80%, or the like. In an embodiment of the present application, the ceramic particles include at least one of zinc oxide, zirconium oxide, aluminum oxide, silicon dioxide, titanium oxide, and silicon carbide. The ceramic particles are high temperature resistant, corrosion resistant, high in hardness and good in strength, and are beneficial to improving the performance of the shell 100.
The hardness of the surface of the polymer ceramic layer 10 is measured under 1kg pressure by using the GB/T6739-1996 standard. In the present embodiment, the pencil hardness of the surface of the polymer ceramic layer 10 is 3H or more. Further, the pencil hardness of the surface of the polymer ceramic layer 10 is 3H-7H, so that the hardness and the strength of the shell 100 are greatly improved. Further, the pencil hardness of the surface of the polymer ceramic layer 10 is 4H to 7H. Specifically, the pencil hardness of the surface of the polymer ceramic layer 10 may be, but is not limited to, 3H, 4H, 5H, 6H, 7H, or the like.
The Vickers hardness of the polymer ceramic layer 10 is detected under the pressure of 1kg by adopting the GB/T16534-2009 standard. In the present embodiment, the vickers hardness of the polymer ceramic layer 10 is greater than or equal to 400HV. Further, the polymer ceramic layer 10 has a Vickers hardness of 400HV to 800HV. Further, the polymer ceramic layer 10 has a Vickers hardness of 500HV to 700HV. Specifically, the vickers hardness of the polymer ceramic layer 10 may be, but is not limited to, 400HV, 450HV, 500HV, 550HV, 600HV, 700HV, or 800HV, etc.
In the present application, the falling ball impact performance test is used to test the performance of the polymer ceramic layer 10, wherein the falling ball is a 32g stainless steel ball, and the thickness of the polymer ceramic layer 10 is 0.8mm. In one embodiment, the polymer ceramic layer 10 is supported on the fixture, wherein the polymer ceramic layer 10 has a support of 5mm at the periphery and a suspended middle part; and (3) freely dropping a 32g stainless steel ball from a certain height to a point to be detected on the surface of the polymer ceramic layer 10 to be detected, and recording the height of the broken polymer ceramic layer 10 as the ball dropping height. Further, a 32g stainless steel ball is freely dropped to the center of the surface of the polymer ceramic layer 10 to be tested from a certain height, each height is tested for 5 times, and the height for breaking the polymer ceramic layer 10 is recorded as the ball drop height. In the present embodiment, the polymer ceramic layer 10 has a ball drop height of 70cm or more. Further, the polymer ceramic layer 10 has a ball falling height of 70cm to 100cm. Further, the polymer ceramic layer 10 has a ball drop height of 80cm to 95cm. The polymer ceramic layer 10 has excellent drop resistance and strong toughness.
The four-point bending strength of the polymer ceramic layer 10 is detected by adopting the GB/T6569-2006 standard. In the present embodiment, the four-point bending strength of the polymer ceramic layer 10 is greater than or equal to 400N. Further, the four-point bending strength of the polymer ceramic layer 10 is 400N-800N. Further, the polymer ceramic layer 10 has a Vickers hardness of 500N to 750N. Specifically, the four-point bending strength of the polymer ceramic layer 10 may be, but is not limited to, 400N, 450N, 500N, 600N, 650N, 700N, 750N, or the like.
In the present application, the polymer ceramic layer 10 is placed on an extrusion jig, the top end of a spherical compressive head with a diameter of 10mm is aligned with the middle position of the polymer ceramic layer 10, the polymer ceramic layer 10 is pressed at a compression speed of 5mm/min until the polymer ceramic layer 10 is broken, and the peak pressure value at this time is recorded as the extrusion force. In the embodiment of the present application, the pressing force of the polymer ceramic layer 10 is greater than or equal to 500N. Further, the pressing force of the polymer ceramic layer 10 is 500N to 700N. Further, the pressing force of the polymer ceramic layer 10 is 550N-650N. Specifically, the pressing force of the polymer ceramic layer 10 may be, but is not limited to, 500N, 550N, 570N, 600N, 650N, 680N, 700N, or the like.
In the present embodiment, the polymer ceramic layer 10 may further include a colorant, so that the housing 100 has a different color appearance, thereby improving the visual effect. Specifically, the colorant may be, but is not limited to, at least one selected from carbon black, iron oxide, cobalt oxide, cerium oxide, nickel oxide, bismuth oxide, zinc oxide, manganese oxide, chromium oxide, copper oxide, vanadium oxide, and tin oxide, respectively. In one embodiment, the mass content of the colorant in the polymer ceramic layer 10 is less than or equal to 15%, so that the color of the polymer ceramic layer 10 can be improved without affecting the content of the ceramic particles. Further, the mass content of the colorant in the polymer ceramic layer 10 is 0.5% -10%.
Referring to fig. 5, which is a schematic structural diagram of a housing according to another embodiment of the present disclosure, the housing 100 may further include a protective layer 20, and the protective layer 20 is disposed on the surface of the polymer ceramic layer 10. The housing 100 has an inner surface and an outer surface opposite to each other during use, and the protective layer 20 is disposed on the outer surface side to protect the housing 100 during use. Specifically, the protective layer 20 may be, but is not limited to, an anti-fingerprint layer, a hardened layer, and the like. Specifically, the thickness of the protective layer 20 may be, but is not limited to, 0.5 μm to 3 μm. In one embodiment, the protective layer 20 comprises an anti-fingerprint layer. Optionally, the anti-fingerprint layer has a contact angle greater than 105 °. The contact angle is an important parameter for measuring the wettability of the liquid on the surface of the material, and the contact angle of the anti-fingerprint layer is larger than 105 degrees, which shows that the liquid can easily move on the anti-fingerprint layer, thereby avoiding the pollution on the surface of the anti-fingerprint layer and having excellent anti-fingerprint performance. Optionally, the anti-fingerprint layer comprises a fluorine-containing compound. Specifically, the fluorine-containing compound may be, but not limited to, a fluorosilicone polymer, perfluoropolyether, fluoroacrylate, and the like. Further, the anti-fingerprint layer also comprises silicon dioxide, and the friction resistance of the anti-fingerprint layer is further improved by adding the silicon dioxide. In another embodiment, the protective layer 20 comprises a hardened layer. The surface hardness and scratch resistance of the case 100 are further improved by providing the hardened layer. Optionally, the material of the hardened layer includes at least one of graphite, alumina, zirconia, silica, chromium nitride, and titanium nitride.
In the present application, the thickness of the housing 100 may be selected according to the requirements of the application scenario, which is not limited herein; in one embodiment, the housing 100 may be used as a casing, a middle frame, a decoration, etc. of the electronic device 200, such as a casing of a mobile phone, a tablet computer, a notebook computer, a watch, an MP3, an MP4, a GPS navigator, a digital camera, etc. The housing 100 in the embodiment of the present application may have a 2D structure, a 2.5D structure, a 3D structure, and the like, which may be specifically selected as needed. In one embodiment, when the housing 100 is used as a mobile phone rear cover, the thickness of the housing 100 is 0.5mm to 1.2mm. Specifically, the thickness of the housing 100 may be, but is not limited to, 0.6mm, 0.7mm, 0.8mm, 0.9mm, 1mm, 1.1mm, or 1.2mm. In another embodiment, when the casing 100 is used as a mobile phone rear cover, the casing 100 includes a main body and an extension portion disposed at an edge of the main body, and the extension portion is bent toward the main body; at this time, the housing 100 is curved.
In the present embodiment, the surface roughness of the case 100 is less than 0.1 μm. By providing the housing 100 with small surface roughness, the ceramic texture of the housing can be enhanced, and the visual effect can be improved. Further, the surface roughness of the case 100 is 0.02 μm to 0.08 μm. In the embodiments of the present application, the caseThe density of the body 100 is less than or equal to 2.6g/cm 3 . Further, the density of the case 100 is 2.3g/cm 3 -2.6g/cm 3 . The application provides a casing 100 density is little, is favorable to satisfying the development demand of frivolousization.
The following provides further explanation of the method for manufacturing the housing and the performance of the housing obtained by the method of the present application through specific examples and comparative examples.
Example 1
A method of making a housing comprising:
mixing spherical zinc oxide with the grain size of 100nm-150nm and spherical aluminum oxide with the grain size of 100-200nm according to the mass ratio of 10; mixing 20kg of composite ceramic particles, a silane coupling agent accounting for 1% of the mass of the composite ceramic particles, polyvinyl alcohol accounting for 0.5% of the mass of the composite ceramic particles and carbon black accounting for 2% of the mass of the composite ceramic particles to obtain a mixed material; adding water and alumina grinding beads into the mixed material, wherein the mass ratio of the mixed material to the water to the ball grinding beads is 1. And carrying out spray drying granulation on the mixed slurry to obtain the treated ceramic particles, wherein the feeding temperature is 80 ℃, the air inlet temperature is 150 ℃, the air exhaust temperature is 80 ℃, the temperature in the tower is 85 ℃, and the negative pressure in the tower is 100pa. Mixing the treated ceramic particles and the polymer according to a mass ratio of 8:2 mixing to form a mixture, the polymer comprising polyphenylene sulfide and polyphenylene sulfone; the mixture was placed in a blending extruder, blended 3 times, and then extruded for pelletization to obtain an injection-molded feed. Drying the injection molding feed at 120 ℃ for 12h, and then adding the injection molding feed into an injection machine for injection molding; the molding temperature is 345 ℃, the injection speed is 90%, the injection pressure is 200MPa, the mold temperature is 145 ℃, and the pressure maintaining time is 30s, so as to prepare the polymer ceramic blank.
Mixing melamine and zinc according to a mass ratio of 6. And uniformly coating the pretreatment liquid on a polymer ceramic blank in a coating mode, and drying at 80 ℃ to form a pretreatment layer to obtain a composite blank.
Placing the composite blank into a jig, and then placing the jig and the composite blank into an oven to carry out heat treatment according to the following curve: heating the mixture to 250 ℃ at room temperature for 1h, and keeping the temperature at 250 ℃ for 1h; raising the temperature from 250 ℃ to 330 ℃ for 1h, preserving the heat at 330 ℃ for 2h, and then naturally cooling to obtain a first green body. And (3) putting the first green body into a hot-pressing sintering furnace for hot pressing, wherein the hot pressing temperature is 360 ℃, the heat preservation time is 4 hours, the hot pressing pressure is 40MPa, the hot pressing atmosphere is nitrogen, and naturally cooling after the hot pressing is finished to obtain a second green body.
CNC machining is carried out on the second blank according to a product drawing, a PCD milling cutter is selected for CNC machining, the rotating speed of a main shaft is 22000rpm, and the single cutting amount is 50 micrometers; then, rough polishing is carried out by a polishing machine, a polishing disc is made of pig hair matched with a buffing composite material, rough polishing liquid is water-based diamond polishing liquid, the granularity of diamond micro powder in the rough polishing liquid is 2 mu m, and the concentration of the rough polishing liquid is 10wt%; and after rough polishing, performing fine polishing by using a polishing machine, wherein the granularity of silicon oxide in the fine polishing liquid is 200nm, and the concentration of the fine polishing liquid is 40wt%, so that a pretreatment layer is removed, a polymer ceramic layer is obtained, and the shell is prepared.
Example 2
The difference from example 1 is that after the polymer ceramic layer is prepared, a hardened layer is plated on the surface of the polymer ceramic layer by means of evaporation plating, the material of the hardened layer is alumina, the thickness of the hardened layer is 1 μm, and then the anti-fingerprint layer is plated on the surface of the hardened layer to prepare the shell.
Comparative example 1
A zirconia ceramic shell is formed by sintering a zirconia ceramic blank.
Comparative example 2
The shell was prepared according to the method shown in example 1 of patent CN 108483991A.
Comparative example 3
Substantially the same as in example 1, except that the spray coating of the pretreatment liquid was not performed, the polymer ceramic body was directly subjected to the heat treatment.
Comparative example 4
Substantially the same as in comparative example 3, except that the heat treatment process comprised heating to 250 ℃ at room temperature for 1 hour, and holding at 250 ℃ for 24 hours; the temperature is raised from 250 ℃ to 330 ℃ for 1h, and the temperature is kept at 330 ℃ for 24h.
Performance detection
The cases obtained in examples and comparative examples were subjected to tests of pencil hardness, vickers hardness, ball drop height, four-point bending strength, pressing force, and density according to the test methods described in the specification, and the results are shown in table 1, in which the thicknesses of the cases obtained in examples and comparative examples were kept uniform in each test.
TABLE 1 Performance test results
Figure BDA0003205538880000151
The pencil hardness and the vickers hardness of the shell are high, the shell has excellent scratch resistance, meanwhile, the falling ball height is high, the four-point bending strength is high, the extrusion force is strong, the shell has excellent toughness and strength, and the overall density is low. Compared with comparative example 1, the overall toughness of the shell provided by the embodiment of the application is improved, and the density is reduced; compared with comparative examples 2-4, the surface hardness and the overall strength of the shell provided by the embodiment of the application are greatly improved, and the application of the shell is facilitated.
The present application further provides an electronic device 200 including the housing 100 in any of the above embodiments. It is understood that the electronic device 200 may be, but is not limited to, a mobile phone, a tablet computer, a notebook computer, a watch, an MP3, an MP4, a GPS navigator, a digital camera, etc. Please refer to fig. 6, which is a schematic structural diagram of an electronic device according to an embodiment of the present disclosure, wherein the electronic device 200 includes a housing 100. The housing 100 can improve the strength and the surface hardness of the electronic device 200, and the electronic device 200 has an appearance with a ceramic texture and excellent product competitiveness. Referring to fig. 7, which is a schematic structural diagram of an electronic device according to an embodiment of the present disclosure, a structure of the electronic device 200 may include an RF circuit 210, a memory 220, an input unit 230, a display unit 240, a sensor 250, an audio circuit 260, a WiFi module 270, a processor 280, a power supply 290, and the like. The RF circuit 210, the memory 220, the input unit 230, the display unit 240, the sensor 250, the audio circuit 260, and the WiFi module 270 are respectively connected to the processor 280; the power supply 290 is used to supply power to the entire electronic device 200. Specifically, the RF circuit 210 is used for transmitting and receiving signals; the memory 220 is used for storing data instruction information; the input unit 230 is used for inputting information, and may specifically include a touch panel and other input devices such as operation keys; the display unit 240 may include a display screen or the like; the sensor 250 includes an infrared sensor, a laser sensor, etc. for detecting a user approach signal, a distance signal, etc.; the speaker 261 and the microphone 262 are connected with the processor 280 through the audio circuit 260, and are used for receiving and transmitting sound signals; the WiFi module 270 is configured to receive and transmit WiFi signals; the processor 280 is used for processing data information of the electronic device 200.
The foregoing detailed description has provided for the purposes of providing a thorough understanding of the present embodiments, and has illustrated and described the principles and embodiments of the present application, but it is to be understood that this disclosure is only illustrative of the methods and their core concepts; meanwhile, for a person skilled in the art, according to the idea of the present application, the specific embodiments and the application range may be changed. In view of the above, the description should not be taken as limiting the application.

Claims (13)

1.一种壳体的制备方法,其特征在于,包括:1. A preparation method for a shell, characterized in that, comprising: 将聚合物陶瓷坯体涂覆和/或浸泡前处理液,经干燥后在所述聚合物陶瓷坯体表面形成前处理层,得到复合坯体,其中,所述聚合物陶瓷坯体包括聚合物,所述前处理液包括能够促进所述聚合物交联的促进剂;Coating and/or immersing the polymer ceramic body in a pretreatment liquid, forming a pretreatment layer on the surface of the polymer ceramic body after drying, to obtain a composite body, wherein the polymer ceramic body includes polymer , the pretreatment liquid includes an accelerator capable of promoting crosslinking of the polymer; 所述复合坯体经过热处理和热压后,再去除所述前处理层,得到聚合物陶瓷层,制得壳体。After the composite green body is heat-treated and hot-pressed, the pre-treatment layer is removed to obtain a polymer ceramic layer and a casing. 2.如权利要求1所述的制备方法,其特征在于,所述前处理液中所述促进剂的质量含量为10%-50%。2. The preparation method according to claim 1, characterized in that, the mass content of the accelerator in the pretreatment liquid is 10%-50%. 3.如权利要求1所述的制备方法,其特征在于,所述促进剂包括有机促进剂和金属促进剂中的至少一种;3. preparation method as claimed in claim 1, is characterized in that, described accelerator comprises at least one in organic accelerator and metal accelerator; 所述有机促进剂包括三聚氰胺、六甲氧甲基三聚氰胺、三羟基苯、季戊四醇三烯丙基醚、苯酚和受阻酚类中的至少一种,所述金属促进剂包括银、铜、铁、铅、锌和镁中的至少一种。The organic accelerator includes at least one of melamine, hexamethoxymethyl melamine, trihydroxybenzene, pentaerythritol triallyl ether, phenol and hindered phenols, and the metal accelerator includes silver, copper, iron, lead, at least one of zinc and magnesium. 4.如权利要求3所述的制备方法,其特征在于,所述促进剂中所述有机促进剂和所述金属促进剂的质量比为1.2-4。4. The preparation method according to claim 3, characterized in that, the mass ratio of the organic accelerator and the metal accelerator in the accelerator is 1.2-4. 5.如权利要求1所述的制备方法,其特征在于,所述前处理液还包括分散剂、粘结剂和溶剂,所述前处理液中所述分散剂的质量含量为0.5%-5%,所述粘结剂的质量含量为1%-5%,所述溶剂的质量含量为50%-80%;5. preparation method as claimed in claim 1 is characterized in that, described pretreatment liquid also comprises dispersant, binding agent and solvent, and the mass content of described dispersant in described pretreatment liquid is 0.5%-5% %, the mass content of the binder is 1%-5%, and the mass content of the solvent is 50%-80%; 所述分散剂包括硅烷偶联剂、硬脂酸、硬脂酸铵和聚乙二醇中的至少一种,所述粘结剂包括聚乙烯醇、聚乙烯醇缩丁醛酯、聚乙二醇和丙烯酸树脂中的至少一种,所述溶剂包括水、乙醇和丙酮中的至少一种。The dispersant includes at least one of silane coupling agent, stearic acid, ammonium stearate and polyethylene glycol, and the binder includes polyvinyl alcohol, polyvinyl butyral ester, polyethylene glycol At least one of alcohol and acrylic resin, the solvent includes at least one of water, ethanol and acetone. 6.如权利要求1所述的制备方法,其特征在于,所述热处理的时间小于或等于12h。6. The preparation method according to claim 1, characterized in that, the time of the heat treatment is less than or equal to 12h. 7.如权利要求6所述的制备方法,其特征在于,所述热处理包括在0.5h-1h内从15℃-40℃升温至220℃-280℃后保温0.5h-2h,再在0.5h-1h内从220℃-280℃升温至300℃-380℃后保温0.5h-4h;所述热处理的温度大于所述聚合物的熔融温度且小于所述聚合物的分解温度。7. The preparation method according to claim 6, characterized in that, the heat treatment includes heating from 15°C-40°C to 220°C-280°C within 0.5h-1h and then keeping it warm for 0.5h-2h, and then -Raising the temperature from 220°C-280°C to 300°C-380°C within 1 hour and then keeping it warm for 0.5h-4h; the temperature of the heat treatment is higher than the melting temperature of the polymer and lower than the decomposition temperature of the polymer. 8.如权利要求1所述的制备方法,其特征在于,所述涂覆和/或浸泡包括在15℃-40℃下处理1h-2h,所述干燥的温度为80℃-100℃,所述前处理层的厚度为10μm-100μm。8. The preparation method according to claim 1, characterized in that, the coating and/or soaking includes treatment at 15°C-40°C for 1h-2h, the drying temperature is 80°C-100°C, the The thickness of the pretreatment layer is 10 μm-100 μm. 9.如权利要求1所述的制备方法,其特征在于,所述热压包括在20MPa-80MPa、300℃-400℃下处理2h-12h,所述热压的温度大于所述聚合物的玻璃化转变温度且小于所述聚合物的分解温度。9. The preparation method according to claim 1, characterized in that, the hot pressing includes treating at 20MPa-80MPa, 300°C-400°C for 2h-12h, and the temperature of the hot pressing is higher than that of the polymer glass transition temperature and less than the decomposition temperature of the polymer. 10.如权利要求1所述的制备方法,其特征在于,所述聚合物陶瓷坯体的制备,包括:10. The preparation method according to claim 1, wherein the preparation of the polymer ceramic body comprises: 陶瓷颗粒与所述聚合物混合后,经造粒得到注塑喂料;After the ceramic particles are mixed with the polymer, the injection molding feed is obtained through granulation; 所述注塑喂料经注塑得到聚合物陶瓷坯体。The injection molding feed is injected to obtain a polymer ceramic green body. 11.一种壳体,其特征在于,通过权利要求1-10任一项所述的制备方法制得,所述壳体包括聚合物陶瓷层。11. A housing, characterized in that it is manufactured by the preparation method according to any one of claims 1-10, and the housing comprises a polymer ceramic layer. 12.如权利要求11所述的壳体,其特征在于,所述聚合物陶瓷层中,所述聚合物交联形成网状结构,所述陶瓷颗粒分散在所述网状结构中;12. The casing according to claim 11, wherein in the polymer ceramic layer, the polymer is cross-linked to form a network structure, and the ceramic particles are dispersed in the network structure; 所述聚合物陶瓷层包括陶瓷颗粒和聚合物,所述陶瓷颗粒包括氧化锌、氧化锆、氧化铝、二氧化硅、氧化钛和碳化硅中的至少一种,所述陶瓷颗粒的直径为20nm-1μm,所述聚合物包括聚苯硫醚、聚亚苯基砜、聚酰胺和乙烯-醋酸乙烯共聚物中的至少一种。The polymer ceramic layer includes ceramic particles and polymers, the ceramic particles include at least one of zinc oxide, zirconium oxide, aluminum oxide, silicon dioxide, titanium oxide and silicon carbide, and the diameter of the ceramic particles is 20nm -1 μm, the polymer includes at least one of polyphenylene sulfide, polyphenylene sulfone, polyamide and ethylene-vinyl acetate copolymer. 13.一种电子设备,其特征在于,包括权利要求11-12任一项所述的壳体。13. An electronic device, comprising the casing according to any one of claims 11-12.
CN202110917644.7A 2021-08-10 2021-08-10 Shell, preparation method thereof and electronic equipment Active CN113683439B (en)

Priority Applications (1)

Application Number Priority Date Filing Date Title
CN202110917644.7A CN113683439B (en) 2021-08-10 2021-08-10 Shell, preparation method thereof and electronic equipment

Applications Claiming Priority (1)

Application Number Priority Date Filing Date Title
CN202110917644.7A CN113683439B (en) 2021-08-10 2021-08-10 Shell, preparation method thereof and electronic equipment

Publications (2)

Publication Number Publication Date
CN113683439A CN113683439A (en) 2021-11-23
CN113683439B true CN113683439B (en) 2022-10-28

Family

ID=78579371

Family Applications (1)

Application Number Title Priority Date Filing Date
CN202110917644.7A Active CN113683439B (en) 2021-08-10 2021-08-10 Shell, preparation method thereof and electronic equipment

Country Status (1)

Country Link
CN (1) CN113683439B (en)

Families Citing this family (1)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN114554766B (en) * 2022-03-11 2023-11-07 Oppo广东移动通信有限公司 Shell, manufacturing method thereof and electronic equipment

Citations (7)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN105282999A (en) * 2014-07-09 2016-01-27 Abb技术有限公司 Enclosure
US20180070463A1 (en) * 2016-09-06 2018-03-08 Apple Inc. Multi-Colored Ceramic Housings for an Electronic Device
CN110191606A (en) * 2019-06-05 2019-08-30 Oppo广东移动通信有限公司 Electronic equipment cover plate, preparation method thereof and electronic equipment
CN110612326A (en) * 2017-04-26 2019-12-24 康宁股份有限公司 Transparent composite film with hard coat layer, method for forming the same, and flexible display device including the same
CN111704479A (en) * 2020-06-01 2020-09-25 Oppo广东移动通信有限公司 Surface treatment method of ceramic substrate, ceramic plate, casing and electronic device
CN113105234A (en) * 2021-04-16 2021-07-13 深圳陶陶科技有限公司 Zirconia composite material, ceramic product, preparation method and application thereof
CN113194647A (en) * 2021-04-29 2021-07-30 Oppo广东移动通信有限公司 Shell assembly, preparation method thereof and electronic equipment

Patent Citations (7)

* Cited by examiner, † Cited by third party
Publication number Priority date Publication date Assignee Title
CN105282999A (en) * 2014-07-09 2016-01-27 Abb技术有限公司 Enclosure
US20180070463A1 (en) * 2016-09-06 2018-03-08 Apple Inc. Multi-Colored Ceramic Housings for an Electronic Device
CN110612326A (en) * 2017-04-26 2019-12-24 康宁股份有限公司 Transparent composite film with hard coat layer, method for forming the same, and flexible display device including the same
CN110191606A (en) * 2019-06-05 2019-08-30 Oppo广东移动通信有限公司 Electronic equipment cover plate, preparation method thereof and electronic equipment
CN111704479A (en) * 2020-06-01 2020-09-25 Oppo广东移动通信有限公司 Surface treatment method of ceramic substrate, ceramic plate, casing and electronic device
CN113105234A (en) * 2021-04-16 2021-07-13 深圳陶陶科技有限公司 Zirconia composite material, ceramic product, preparation method and application thereof
CN113194647A (en) * 2021-04-29 2021-07-30 Oppo广东移动通信有限公司 Shell assembly, preparation method thereof and electronic equipment

Also Published As

Publication number Publication date
CN113683439A (en) 2021-11-23

Similar Documents

Publication Publication Date Title
CN113395860B (en) Shell and its preparation method and electronic equipment
CN115604943B (en) Housing, its preparation method, and electronic equipment
CN113347816A (en) Shell, preparation method thereof and electronic equipment
CN105563616B (en) Method for forming zirconia ceramic product
CN105541324A (en) Preparation method of mobile phone casing
CN101451057A (en) Bamboo charcoal base electro-magnetic screen composite material and preparation method thereof
CN108675812B (en) Toughened alumina ceramic mobile phone backboard and preparation method thereof
CN103341918A (en) Resin fret saw and preparation method thereof
WO2023279792A1 (en) Housing and preparation method therefor, and electronic device
CN105481364A (en) Preparation method of ceramic watch case
CN110436921A (en) Ceramic product and its preparation method and electronic device
CN107652456A (en) A kind of preparation method of shape memory cyanate prepreg
CN113395855B (en) Shell, preparation method thereof and electronic equipment
CN113683439A (en) Shell, preparation method thereof and electronic equipment
WO2022252732A1 (en) Polymer ceramic casing and preparation method therefor, and electronic device
CN113321446A (en) Ceramic polymer composite material and preparation method thereof, shell and preparation method thereof, and electronic equipment
CN113402202A (en) Method for preparing shell assembly, shell assembly and electronic device
CN107746275A (en) Black zirconia ceramics and preparation method thereof, mobile phone backboard and mobile phone
CN115710369B (en) Scratch-resistant optical anti-glare film and preparation method thereof
CN113603379B (en) Ceramic composite material, shell, preparation method of shell and electronic equipment
CN113402201B (en) Composite material and preparation method thereof, structural member and preparation method thereof, and electronic equipment
CN114554766B (en) Shell, manufacturing method thereof and electronic equipment
CN113347815B (en) Shell, preparation method thereof and electronic equipment
CN100448571C (en) A kind of injection molding method of CuSn10 alloy
CN115214173A (en) Housing and manufacturing method thereof, and electronic device

Legal Events

Date Code Title Description
PB01 Publication
PB01 Publication
SE01 Entry into force of request for substantive examination
SE01 Entry into force of request for substantive examination
GR01 Patent grant
GR01 Patent grant